Investigation of the Catalytic Performance of a Novel Nickel/Kit-6 Nanocatalyst for the Hydrogenation of Vegetable Oil. (29th February 2012) - Usman, M. A.; Alaje, T. O.; Ekwueme, V. I.; Awe, E. A.
Abstract : Highly ordered mesoporous materials are opening the door to new opportunities in catalysis due to their extraordinary intrinsic features. In this study, Nickel was supported on highly ordered mesoporous silica (KIT-6) by the wet impregnation method, and its performance in the hydrogenation of edible vegetable oil was compared with that of Ni/Activated carbon prepared using the same method as well as with unsupported Nickel. The degree of conversion for the 50 : 50 Ni/KIT-6 was 81%, as compared to the 29% obtained with 50 : 50 Ni/Activated carbons. The conversion was found to improve with an increase in mass of supported Nickel on KIT-6 thus 20 : 80 Ni/KIT-6 and 30 : 70 Ni/KIT-6 produced conversions of 71% and 74%, respectively. Key among the benefits of KIT-6 when used as a support material is the very high surface area, open framework of the 3D bicontinuous interconnected channels, and the well-ordered mesopores which bestow on it an advanced mass transfer characteristics.